A Polypyrrole/Nanoclay Hybrid Film for Ultra-Sensitive Cardiac Troponin T Electrochemical Immunosensor - Landim, Vicente P. A.; Foguel, Marcos V.; Prado, Cecília M.; Sotomayor, Maria P. T. [UNESP]; Vieira, Iolanda C.; Silva, Bárbara V. M.; Dutra, Rosa F. (MDPI, 2022)
An electrochemical immunosensor based on a nanohybrid film of carboxylated polypyrrole and amine nanoclay was developed for label-free detection of the human cardiac troponin T (cTnT). The nanohybrid film was formed in situ on the surface of the glassy carbon electrode, followed by the covalent immobilization of anti-troponin T antibodies by glutaraldehyde. Morphological and chemical characterizations of the nanohybrid film were performed by scanning electron microscopy and Fourier-transform infrared spectroscopy. Under the optimized conditions, a calibration curve for cTnT in spiked serum was obtained by square wave voltammetry, and a low limit of detection and quantification was achieved (0.35 and 1.05 pg mL−1, respectively). This was the first time that this type of nanohybrid film was used in the development of an immunosensor for cTnT that proved to be a simple and efficient strategy for the manufacture of a label-free electrochemical device that could be applied in the diagnosis of acute myocardial infarction.
Keywords: cardiac troponin T; immunosensor; nanoclay; polypyrrole